Pentingnya Kemampuan Bahasa Inggris Sebagai Petunjuk Penggunaan Mesin Bagi Karyawan PT. SAGAMI INDONESIA - Misla Geubrina; Z Zuindra; A Arifuddin; Hendra Mulia (LPPM STIKOM Tunas Bangsa, 2022)
Foreign language ability is one of the skills that must be possessed in this era of globalization, because the world community is required to be able to communicate both orally and in writing, especially in English. English is one of the foreign languages that have an international standard where the whole world with various groups speaks the language. This is also experienced by employees who work in various companies, especially multinational companies or foreign companies. Employees must be able to communicate in the foreign language. The instructions also use English to instruct the use of various products, especially machines. In connection with this, the team of lecturers carried out activities to support the importance of English language skills as instructions for using machines for employees of PT. Indonesian Sagami. In this activity, the lecturers who are members of the community service group help partners to provide material on instructions for using machines to increase the language skills that employees already have. The method of implementing this Community Service activity is done face-to-face through discussion and question and answer methods. The results obtained are expected to add insight and knowledge in the employees' English skills.